The Olfactory Organ Is Populated by Neutrophils and Macrophages During Early Development - Palominos, M. Fernanda; Whitlock, Kathleen E. (Frontiers in Cell and Developmental Biology, 2021)
The immune system of vertebrates is characterized by innate and adaptive immunity that function together to form the natural defense system of the organism. During development innate immunity is the first to become functional and is mediated primarily by phagocytic cells, including macrophages, neutrophils, and dendritic cells. In the olfactory sensory system, the same sensory neurons in contact with the external environment have their first synapse within the central nervous system. This unique architecture presents a potential gateway for the entry of damaging or infectious agents to the nervous system. Here we used zebrafish as a model system to examine the development of the olfactory organ and to determine whether it shares immune characteristics of a host defense niche described in other tissues. During early development both neutrophils and macrophages appear coincident with the generation of the primitive immune cells. The appearance of neutrophils and macrophages in the olfactory organs occurs as the blood and lymphatic vascular system is forming in the same region. Making use of the neurogenic properties of the olfactory organ we show that damage to the olfactory sensory neurons in larval zebrafish triggers a rapid immune response by local and non-local neutrophils. In contrast macrophages, though present in greater numbers, mount a slower response to damage. We anticipate our findings will open new avenues of research into the role of the olfactory-immune response during normal neurogenesis and damage-induced regeneration, and contribute to our understanding of the formation of a potential host defense immune niche in the peripheral nervous system.